Control of Polymorphism and Morphology in Solution Sheared Organic Field‐Effect Transistors - Galindo, Sergi; Tamayo, Adrián; Leonardi, Francesca; Mas‐Torrent, Marta (Advanced functional materials, 2017)
During the last decades, small molecule organic semiconductors have been successfully used as active layer in organic field‐effect transistors (OFETs). Despite the high mobility achieved so far with organic molecules, in order to progress in the field it is crucial to find techniques to process them from solution. The device reproducibility is one of the principal weak points of organic electronics for further commercialization. To achieve a high device‐to‐device reproducibility it is essential to control the morphology and polymorphism of the active layer for OFET application. In this work, the preparation of thin films is reported based on blends of the organic semiconductor dibenzo‐tetrathiafulvalene (DB‐TTF) and polystyrene by a solution shearing technique compatible with upscaling. Here, it is demonstrated that varying the deposition parameters (i.e., speed and temperature) or the solution formulation (i.e., semiconductor/binder polymer ratio) is possible to control the film morphology and semiconductor polymorphism and, hence, the different intermolecular interactions. It is demonstrated that the control of the thermodynamics and kinetics of the crystallization process is key for the device performance optimization. Further, this is the first time that DB‐TTF thin films of the α‐polymorph are reported. Printed organic semiconductors require high control of polymorphism and morphology to enhance device reproducibility. Thin‐film organic field‐effect transistors have been prepared by solution shearing using blends of a small molecule semiconductor and a binder polymer. The deposition parameters and solution formulation determine the thin‐film morphology and polymorphism, which, in turn, has a crucial impact on the device performance.